The Rich in the "Epistle of Enoch" and the Epistle of James: A Comparative Analysis - Muszytowska, Dorota (The Biblical Annals, 2025)
The article deals with the problem of critical assessment of the negative behaviour of wealthy people, taken up in two different works: the Epistle of Enoch (1 En. 92–105) and the Epistle of James. Due to the incomplete surviving Aramaic and Greek versions of the Epistle of Enoch, which could be a potential source for the author of the Epistle of James, diachronic research would not be fruitful. A comparative analysis in a synchronic approach was used to examine whether one can talk about the dependence or identity of the approach represented in the Epistle of James on the concept of wealth and the rich from the Epistle of Enoch. The conducted analyses indicate far-reaching analogies between these texts. The authors judge the rich by looking at their actions, considering the purpose of human life and the eschatological purpose. The authors are united by the concept of understanding man and his relationship with God and other people. Despite the different persuasive goals of their works, both stigmatise attitudes that oppose God’s will, and their substantively rich sins catalogues can be considered convergent. Both authors point to the irrevocable judgement of God, which includes the punishment of destruction for the rich criticized in those works.